2013
DOI: 10.1021/pr300662j
|View full text |Cite
|
Sign up to set email alerts
|

An iTRAQ Proteomic Study Reveals an Association between Diet-Induced Enhanced Fatty Acid Metabolism and the Development of Glucose Intolerance in Prediabetic Mice

Abstract: High-fat diet (HFD)-induced glucose intolerance and insulin resistance increases the chances of developing type-2 diabetes and cardiovascular disease. To study the mechanism(s) by which a HFD impairs glucose tolerance, we used a quantitative proteomic platform that integrated pI-based OFFGEL fractionation and iTRAQ labeling to profile the temporal changes in adipose membrane protein expression in mice fed a HFD for up to 8 months. Within 2 months of starting the diet, the mice adipose and liver tissues accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 61 publications
1
19
1
Order By: Relevance
“…We previously reported that persistent HFD feeding resulted in fatty liver, and overexpression of Cpt 1A as well as decrease in glycogen storage ability in hepatocytes accounted for liver-related glucose impairment and insulin resistance (30). Here, MSCs did not alter the morphology (Fig.…”
Section: Prevention Of Fatty Liver Development and Restoration Of Hepmentioning
confidence: 58%
See 4 more Smart Citations
“…We previously reported that persistent HFD feeding resulted in fatty liver, and overexpression of Cpt 1A as well as decrease in glycogen storage ability in hepatocytes accounted for liver-related glucose impairment and insulin resistance (30). Here, MSCs did not alter the morphology (Fig.…”
Section: Prevention Of Fatty Liver Development and Restoration Of Hepmentioning
confidence: 58%
“…In an HFD-induced fatty liver, a massive amount of saturated fatty acids accumulated in hepatocytes results in insulin resistance via inhibiting insulin signaling through a c-Jun N-terminal kinase-dependent mechanism (9,40) and turning off glucose metabolism in hepatocytes with active b-oxidation (30). Systemic MSC transplantation restored insulin sensitivity in the liver by preventing fatty liver formation induced by an HFD (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations